2000
DOI: 10.1897/1551-5028(2000)019<2059:dboesa>2.3.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Differential Binding of Endogenous Steroids and Chemicals to Androgen Receptors in Rainbow Trout and Goldfish

Abstract: Abstract-Androgen receptors (ARs) from fish were characterized in order to evaluate differences in the binding affinities of steroids and environmental chemicals between mammals and fish, among species of fish, and among target tissues within a species of fish. High-affinity, low-capacity ARs were identified in cytosolic fractions of rainbow trout brains (Oncorhynchus mykiss) and the brains, ovaries, and testes of goldfish (Carassius auratus) using [ 3 H]testosterone. The binding specificities of endogenous st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
37
0

Year Published

2002
2002
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(37 citation statements)
references
References 0 publications
0
37
0
Order By: Relevance
“…Although estrogens at this concentration can cause sex reversal (Papoulias et al 1999), the comparatively lower affinity of o,p´-DDE and o,p´-DDT for the ER (Nimrod and Benson 1997) suggests that higher exposures of these compounds are required for sex reversal to occur. Nevertheless, o,p´-DDT and o,p´-DDE at low concentrations may interfere with the binding of natural ligands to a variety of steroid binding moieties (e.g., receptors and binding proteins) (Danzo 1997;Donohoe and Curtis 1996;Gaido et al 1997;Kupfer and Bulger 1976;Lundholm 1998;Mason and Schulte 1980;Nimrod and Benson 1997;Shilling and Williams 2000;Wells and Van Der Kraak 2000), thereby allowing for endocrine-disrupting effects.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although estrogens at this concentration can cause sex reversal (Papoulias et al 1999), the comparatively lower affinity of o,p´-DDE and o,p´-DDT for the ER (Nimrod and Benson 1997) suggests that higher exposures of these compounds are required for sex reversal to occur. Nevertheless, o,p´-DDT and o,p´-DDE at low concentrations may interfere with the binding of natural ligands to a variety of steroid binding moieties (e.g., receptors and binding proteins) (Danzo 1997;Donohoe and Curtis 1996;Gaido et al 1997;Kupfer and Bulger 1976;Lundholm 1998;Mason and Schulte 1980;Nimrod and Benson 1997;Shilling and Williams 2000;Wells and Van Der Kraak 2000), thereby allowing for endocrine-disrupting effects.…”
Section: Discussionmentioning
confidence: 99%
“…However, like o,p´-DDT, o,p´-DDE is believed to work through the ER and to have a similar ER agonist potency (Donohoe and Curtis 1996), and exposure to o,p´-DDE has been associated with decreased fecundity and fertility and increased early oocyte atresia (Hose et al 1989). Recently, Wells and Van Der Kraak (2000) showed that o,p´-DDE and o,p´-DDT will also bind to the androgen receptor in goldfish (Carassius auratus) but not rainbow trout (Oncorhynchus mykiss) testes at approximately half the affinity of p,p´-DDE. o,p´-DDE has even been shown to bind to the progesterone receptor in the eggshell gland mucosa of egg-laying ducks and domestic fowl and to the endometrium of the rabbit uterus (Lundholm 1988).…”
mentioning
confidence: 99%
“…To directly investigate the possibility of steroid specificity, we used two steroid receptor antagonists, cyproterone acetate (CA; an anti-androgen) and mifepristone (RU486; an antiglucocorticoid). CA selectively interferes with androgens binding to the androgen receptor in goldfish brain (Wells and Van Der Kraak, 2000) and has been shown to be an effective androgen antagonist in many fish species (Billard, 1982;Kindler et al, 1991;Singh and Joy, 1998;Kiparissis et al, 2003). A more recently developed androgen receptor antagonist, flutamide, does not bind to androgen receptors in teleost brain (Wells and Van Der Kraak, 2000), necessitating the use of CA.…”
Section: Methodsmentioning
confidence: 99%
“…CA selectively interferes with androgens binding to the androgen receptor in goldfish brain (Wells and Van Der Kraak, 2000) and has been shown to be an effective androgen antagonist in many fish species (Billard, 1982;Kindler et al, 1991;Singh and Joy, 1998;Kiparissis et al, 2003). A more recently developed androgen receptor antagonist, flutamide, does not bind to androgen receptors in teleost brain (Wells and Van Der Kraak, 2000), necessitating the use of CA. RU486 is a commonly used glucocorticoid receptor antagonist (it is also an antiprogesterone) and has been shown to interfere with rapid, nongenomic effects of glucocorticoids in other systems (Liu et al, 1995;Roozendaal et al, 2002;He et al, 2003).…”
Section: Methodsmentioning
confidence: 99%
“…Several contaminants have been shown to have the ability to bind to estrogen receptors or androgen receptors, thus disrupting the normal endocrine functions in organisms [1,2]. These endocrine-disrupting chemicals (EDCs) are derived from natural or anthropogenic sources and have been widely detected in sewage treatment plant (STP) effluents [3,4], treated industrial wastewater [5], river surface water [6], and river sediment [7].…”
Section: Introductionmentioning
confidence: 99%